Enhanced Photon Management of Thin‐Film Silicon Solar Cells Using Inverse Opal Photonic Crystals with 3D Photonic Bandgaps. Issue 10 (19th July 2013) - Varghese, Leo T.; Xuan, Yi; Niu, Ben; Fan, Li; Bermel, Peter; Qi, Minghao
<x xml:space="preserve">Abstract</x> Experimental demonstration of silicon inverse opal photonic crystals (PhCs) as a wave‐optics‐based back reflector for polycrystalline silicon solar cells is shown. Using a novel S5 process, crack‐free three dimensional PhCs are fabricated, which are free‐standing and have good optical properties. An efficiency enhancement of 10% is measured for 1.5 μm‐thick commercial silicon solar cells, matching reasonably well with simulations. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>